1969
DOI: 10.1126/science.164.3875.82
|View full text |Cite
|
Sign up to set email alerts
|

Mole Rat Spalax: Evolutionary Significance of Chromosome Variation

Abstract: Four forms of mole rats with diploid numbers of chromosomes of S2, 54, 58, and 60, respectively, were found in Israel and the vicinity. The differences between the chromosome sets are due to whole-arm (Robertsonian) changes and pericentric inversions. The geographic distribution of the different forms is contiguous. Only a few hybrid individuals have been discovered. These chromosome forms are tentatively considered as sibling species, almost completely isolated by cytogenetic and possibly ethological mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

1971
1971
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(56 citation statements)
references
References 2 publications
1
55
0
Order By: Relevance
“…The karyotype of the Mauritious black rats, 2n=42, was apparently evolved from the karyotype of the Oce anian black rats, 2n=38, by centric fission of two pairs of small metacentric chromosome (Yoshida et al 1979). Similar type of species differentiation by centric fission has been re ported in some taxa such as the mole rats (Wahrman et al 1969), the prairie dogs (Nadler and Harris 1967), the root voles (Fredga and Bergstrom 1970), Japanese raccoon dogs (Yoshida and Wada 1984), and others. Todd (1970) suggested that this type of karyotype transforma tion was related to explosive speciation and adaptive radiation of the mammalia.…”
supporting
confidence: 63%
“…The karyotype of the Mauritious black rats, 2n=42, was apparently evolved from the karyotype of the Oce anian black rats, 2n=38, by centric fission of two pairs of small metacentric chromosome (Yoshida et al 1979). Similar type of species differentiation by centric fission has been re ported in some taxa such as the mole rats (Wahrman et al 1969), the prairie dogs (Nadler and Harris 1967), the root voles (Fredga and Bergstrom 1970), Japanese raccoon dogs (Yoshida and Wada 1984), and others. Todd (1970) suggested that this type of karyotype transforma tion was related to explosive speciation and adaptive radiation of the mammalia.…”
supporting
confidence: 63%
“…In many rodents, for example, a combination of asociality manifested in strong individual territoriality, limited adult vagility and juvenile dispersal distance, and patchy distributions can produce the small deme size necessary for rapid chromosomal fixation (29). While specific data on the types of social structuring within various rodent genera are generally not available, the strongly fossorial groups [e.g., pocket gophers (Thomomys, Geomys, and their relatives), mole rats (Spalax), and tucotucos (Ctenomys)] are considered to represent the epitome of this pattern (30,31). These genera are also among the most chromosomally diverse rodents known (32)(33)(34).…”
Section: Resultsmentioning
confidence: 99%
“…Higher rates of karyotype evolution occur in placental mammals (9), small populations (11,43), and species-rich genera (13), with limited mobility (8), as in the Spalacidae (32). The canalization model of chromosomal evolution (10) implies that the karyotype represents an "adaptive strategy" (but see ref.…”
Section: Methodsmentioning
confidence: 99%